A target enrichment probe set for resolving the flagellate land plant tree of life. (24th January 2021) - Breinholt, Jesse W.; Carey, Sarah B.; Tiley, George P.; Davis, E. Christine; Endara, Lorena; McDaniel, Stuart F.; Neves, Leandro G.; Sessa, Emily B.; von Konrat, Matt; Chantanaorrapint, Sahut; Fawcett, Susan; Ickert‐Bond, Stefanie M.; et al.
Abstract : PREMISE: New sequencing technologies facilitate the generation of large‐scale molecular data sets for constructing the plant tree of life. We describe a new probe set for target enrichment sequencing to generate nuclear sequence data to build phylogenetic trees with any flagellate land plants, including hornworts, liverworts, mosses, lycophytes, ferns, and all gymnosperms. METHODS: We leveraged existing transcriptome and genome sequence data to design the GoFlag 451 probes, a set of 56, 989 probes for target enrichment sequencing of 451 exons that are found in 248 single‐copy or low‐copy nuclear genes across flagellate plant lineages. RESULTS: Our results indicate that target enrichment using the GoFlag451 probe set can provide large nuclear data sets that can be used to resolve relationships among both distantly and closely related taxa across the flagellate land plants. We also describe the GoFlag 408 probes, an optimized probe set covering 408 of the 451 exons from the GoFlag 451 probe set that is commercialized by RAPiD Genomics. CONCLUSIONS: A target enrichment approach using the new probe set provides a relatively low‐cost solution to obtain large‐scale nuclear sequence data for inferring phylogenetic relationships across flagellate land plants.